(untitled) (Vietnam Journal of Community Medicine, 2024)
Onychomycosis is one of the most common nail diseases. Treatment of onychomycosis, mainly moderate to severe, can be very challenging, expensive and time consuming. Compared with topical and oral therapies, laser treatment offers a more promising modality for the treatment of severe or resistant cases. To enhance the effect, the combination of oral itraconazole pulse doses with mechanical removal of the affected part of the nail plate by using ablative CO2 laser are investigated. Here, we report a total dystrophic onychomycosis case successfully treated with traditional CO 2 laser and pulse doses itraconazole. This suggests the potential of conventional ablative CO 2 laser in the treatment of severe onychomycosis.